Non-toxic TCaPs modulate osteogenesis via differential protein and gene expression in human osteoblast cells. (2019) - Ibrahim, Shirin; Fazan, Fazilah; Sahid, Sudirman; Seeni, Azman
Abstract: In this study, the effects of a triphasic calcium phosphate bioresorbable beads (TCaPs) on biocompatibility and osteogenesis using L929 fibroblast cells and human osteoblast cells as an in vitro model have been investigated respectively and compared with the commercial MIMIX™ (CMM) and freeze dried human bone (DHB). The results showed that both materials TCaPs and CMM are non-toxic and biocompatible on L929 cells. The levels in MTT assay study of both materials are more than 70% cell viable at 200 mg/ml. L929 cells proliferation of TCaPs and CMM extract are proportional with unexposed medium on all incubation period except on TCaPs extract at day 7. The analysis of osteogenesis on protein level showed there are an expression of alkaline phosphates (ALP) and bone sialoprotein (BSP) on day 3 and 7 of incubation with TCaPs, CMM and DHB extract on osteoblast cell. These results suggest that TCaPs can promote osteoblastic differentiation of human osteoblast, and may be used as bone filler for bone regeneration or drug delivery agent.